Competitiveness of Indonesian Crude Palm Oil ExportsIn The Asean Market (Forum Agribisnis, 2026)
Crude Palm Oil (CPO) is one of Indonesia’s leading export commodities and plays an important role in international trade, particularly in the ASEAN region. However, intense competition among major exporting countries and fluctuations in global market conditions require Indonesia to continuously maintain and strengthen the competitiveness of its CPO exports. This study aims to analyze the competitiveness of Indonesia's crude palm oil (CPO) exports using comparative and competitive approaches. The data used is secondary data for the period 2014-2024 taken from UN Comtrade and BPS with the HS code 151110. The research methods used are Revealed Comparative Advantage (RCA) and Export Competitiveness Index (ECI). The results of the analysis show that Indonesia's RCA CPO value is consistently well above one, which means that Indonesia has a very strong comparative advantage over major competitors such as Malaysia and Thailand. However, the results of the ECI analysis show fluctuations, where some periods have increased and others have decreased, especially in 2021 which showed a significant decrease. This study shows that Indonesia maintains a strong position in the CPO export trade in the ASEAN region despite changes in the market in certain years. Therefore, increasing productivity, production efficiency, and strengthening export strategies are important steps to maintain and enhance the competitiveness of Indonesian CPO in the ASEAN market.